Rising demand for biofuel feedstock: Sweet sorghum's role in future energy markets - Nedumaran, Swamikannu; Habyarimana, Ephrem (2024)
As fossil fuel prices continue to rise and global efforts to reduce greenhouse gas (GHG) emissions accelerate, countries are increasingly incorporating biofuels into their energy strategies and climate action plans. Biofuels, as a renewable energy source, are crucial for addressing the pressing challenges of climate change. With biofuel blending mandates in major economies such as the US, Brazil, China, and India, global biofuel demand is projected to increase from 203 MT in 2024 to 224 MT by 2030. However, the ongoing "food vs. fuel" debate and the need to reduce dependence on food crops like maize, sugarcane, oilseeds, and wheat for biofuel production have heightened the demand for alternative feedstocks. Fossil fuels are non-renewable (not eternal) because they are used up faster than they can be replenished. Sweet sorghum presents, therefore, a strong potential as a 1G and 2G biofuel crop both in oil-importing and exporting nations, and it is expected to improve the livelihoods of smallholder farmers, especially in emerging economies in Asia and Sub-Sharan Africa. Its adaptability to various climates, low input requirements, and dual usage as food, feed, and fuel make it a viable solution for meeting biofuel demand without threatening food security. To capitalize on this emerging market and support the world’s efforts on climate change, ICRISAT developed numerous sweet sorghum varieties and hybrids with high sugar content (16-20 oBrix) suited to diverse agroecological zones, leveraging its modernized breeding pipelines and extensive sorghum genetic resources. These superior materials are continuously shared with farmers and public and private breeding institutions, making an impact.